Implementasi Model Pembelajaran Higher Order Thinking Skills (HOTS) dalam Pendidikan Agama Islam Berbasis Neurosains - Shelsya Azzahra Indriani; Ijudin; Nenden Munawaroh (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Islamic Religious Education currently requires a more interesting and innovative learning approach because competency in Islamic Religious Education subjects is currently still limited to low-level thinking skills, while in the 21st century, students are expected to be able to develop high-level thinking skills. This research aims to develop neuroscience-based Higher Order Thinking Skills in Islamic religious education, including: 1) Understanding how the HOTS learning model in neuroscience-based PAI subjects is implemented in class XII SMAS Asshiddiqiyah. 2) Identify factors that support the implementation of the HOTS learning model in neuroscience-based PAI subjects for class XII SMAS Asshiddiqiyah students. 3) Identifying the obstacles that arise during the implementation of the HOTS learning model in neuroscience-based PAI subjects in class XII SMAS Asshiddiqiyah. 4) Evaluate the effectiveness of the HOTS learning model in neuroscience-based PAI subjects in class XII SMAS Asshiddiqiyah. The approach used in this research is to use a qualitative descriptive approach. The subjects in this research included Islamic Religious Education subject teachers and class XII students at SMAS Asshiddiqiyah. Data collection techniques used in this research include interviews, observation and documentation. The results of this research show that Neuroscience-based Higher Order Thinking Skills in Islamic Religious Education can be developed by utilizing cognitive abilities, such as analysis, evaluation and creativity, which are applied in education. This research contributes to the development of Islamic ideas and concepts in Islamic Religious Education at the high school level.